1991
DOI: 10.1128/jb.173.1.23-27.1991
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes and gene products whose expression is activated during nitrogen-limited growth in Bacillus subtilis

Abstract: The levels of urease and asparaginase were elevated 25-and 20-fold, respectively, in extracts of Bacillus subtilis cells grown in medium containing nitrogen sources that are poor sources of ammonium (NH4+) compared with the levels seen in extracts of cells grown in medium containing nitrogen sources that are good sources of NH4+. To determine whether a collection of genes whose expression responds to nitrogen availability could be isolated, a library of Tn917-lacZ insertions was screened for nitrogen-regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 20 publications
10
88
0
1
Order By: Relevance
“…However, it had significant (p < 0.05), non-zero total ammonia activity especially in UB-2 medium. These observations are consistent with previously published literature linking total ammonia production to urea breakdown from urease, when urea is the sole source of nitrogen and urease is the assumed main catabolic enzyme; the enzyme expressed constitutively in species of Sporosarcina (Mobley et al, 1995) (Mobley and Hausinger, 1989) and B. subtilis (Cruz-Ramos et al,1997; see also Atkinson and Fisher, 1991). This is indeed suggested by our data as it was observed for B. subtilis, B. megaterium and L. sphaericus that increased total ammonia production reached significantly (p<0.05) higher values in UB-2 media compared to near zero values in UB-1 with yeast extract as a co-nitrogen source.…”
Section: Environmental Durability Of Micpsupporting
confidence: 92%
See 1 more Smart Citation
“…However, it had significant (p < 0.05), non-zero total ammonia activity especially in UB-2 medium. These observations are consistent with previously published literature linking total ammonia production to urea breakdown from urease, when urea is the sole source of nitrogen and urease is the assumed main catabolic enzyme; the enzyme expressed constitutively in species of Sporosarcina (Mobley et al, 1995) (Mobley and Hausinger, 1989) and B. subtilis (Cruz-Ramos et al,1997; see also Atkinson and Fisher, 1991). This is indeed suggested by our data as it was observed for B. subtilis, B. megaterium and L. sphaericus that increased total ammonia production reached significantly (p<0.05) higher values in UB-2 media compared to near zero values in UB-1 with yeast extract as a co-nitrogen source.…”
Section: Environmental Durability Of Micpsupporting
confidence: 92%
“…3). This is as expected; B. subtilis is a non-ureolytic organism in the 'good nitrogen' (Atkinson and Fisher, 1991) The presence of crystals as rhombohedra was observed (Fig. 5) along sand granules treated with S. ureae providing credence to the idea that it is capable of inducing prevalent organized formation of secondary minerals 595 (Fig.…”
Section: Environmental Durability Of Micpsupporting
confidence: 78%
“…Although GlnR is the major regulator of glnA expression, the TnrA regulon is comprised primarily of genes required for the utilization of alternative nitrogen sources (3,22). Previous studies have shown that as bacterial growth becomes progressively more nitrogenrestricted, GS expression is derepressed before the pathways for the catabolism of nitrogen-containing compounds are expressed at high levels (8,34,35). The observation that FBI-GS interacts less tightly with GlnR than with TnrA provides a molecular explanation for this pattern of gene regulation in B. subtilis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the experimental system with B. subtilis no decrease in urea concentration was detected. Although physiologic information (Atkinson and Fisher, 1991) and genomic information (Cruz-Ramos et al, 1997) confirm the presence of urease and urease genes in B. subtilis 186, this organism did not exhibit ureolytic activity under the conditions of these experiments, and therefore was a suitable nonureolytic control. The initial drop in pH observed with the B. subtilis may have been attributable simply to the initial mixing of the experimental solutions; the B. subtilis cell suspension was at pH 6.5 before mixing with the 2Ï« synthetic groundwater.…”
Section: Solution Chemistry Changesmentioning
confidence: 99%